Retrospective Study of Neoplasms in Domestic Animals: a Survey Between 1993 and 2002 of the Service of Animal Pathology, Department of Pathology, School of Veterinary Medicine and Animal Science, University of Sao Paulo, Southeast Brazil - Kimura, Kátia Cristina; Gárate, Ana Paula; Dagli, Maria Lúcia Zaidan (Brazilian Journal of Veterinary Pathology, 2012)
The incidence of neoplasia in animals is increasing, and cancer epidemiology can be considered an essential area in veterinary pathology and clinics. The aim of this study was to present a survey of neoplasia in domestic animals diagnosed at the Animal Pathology Service (Serviço de Patologia Animal – SPA), Department of Pathology, School of Veterinary Medicine and Animal Science of the University of São Paulo, Brazil. Biopsy and necropsy archival specimens of the SPA were surveyed and all cases with the main diagnosis of neoplasia from 1993 to 2002 were retrieved. Animal species, breed, age, gender, location, and the histological type of neoplasm were recorded and the findings analyzed and formatted to display the epidemiological features of the tumors. A total of 12.118 biopsy and necropsy specimens were processed by the diagnostic service during this period. Among them, 1.971 cases (16%) of neoplasia were found. Most cases of neoplasia were diagnosed in canines (92%, n=1.813), followed by felines (4%, n=82), equines (3%, n=61) and bovines (1%, n=15). Cross breed was the most commonly found breed among dogs (27%, n=492) and cats (40%, n=33). Holstein (47%, n=7) and Mangalarga (28%, n=17) were the most commonly affected breeds in bovines and equines, respectively. The gender incidence of tumors was not significantly different in any species. Dogs, cats and horses were more frequently affected by neoplasia at the age range of 6 to 10 years while cattle were affected at an age range of 1 to 10 years. The most diagnosed neoplasm in dogs was mammary carcinoma (13%, n=244) whereas squamous cell carcinoma was the most diagnosed neoplasm in cats (18%, n=14), cattle (53%, n=8), and horses (33%, n=5). Due to the absence of a veterinary cancer registry in Brazil, epidemiological studies may represent important sources of information on neoplasia in animals, and, additionally, may be a tool in the development of prevention methods in order to control cancer in domestic animals.